2021
DOI: 10.47583/ijpsrr.2021.v70i01.012
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Herbal Naturopathy

Abstract: Modern medicinal practice is widely followed nowadays which is providing the quick treatment but lacking and even showing hazardous signs in the long run. Naturopathy treats the body by bringing us close to nature. Naturopathy works on the route of suffering and treats it naturally. Human body is made up from five basic elements of nature. So, harmony has to be maintained between nature to live a healthy life. Imbalance of these natural elements will cause diseased states. So, naturopathy is a very effective h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Some herbs, such as aloe vera and senna, have laxative effects that can cause diarrhoea (Ashfaq & Yousaf, 2022). Alotiby et al, 2021 identi ed Stomach pain in this review as a major side effect of herbal medicine use, particularly if the herbs are taken on an empty stomach or in large amounts, a nding corroborated by Tripathi & Bahuguna (2022). Sweating, headache, and nausea/vomiting are other common side effects of natural products cited in this review by Alonso-Castro et al, 2021, Alotiby et al, 2021 andKurniasih &Juwita (2021).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Some herbs, such as aloe vera and senna, have laxative effects that can cause diarrhoea (Ashfaq & Yousaf, 2022). Alotiby et al, 2021 identi ed Stomach pain in this review as a major side effect of herbal medicine use, particularly if the herbs are taken on an empty stomach or in large amounts, a nding corroborated by Tripathi & Bahuguna (2022). Sweating, headache, and nausea/vomiting are other common side effects of natural products cited in this review by Alonso-Castro et al, 2021, Alotiby et al, 2021 andKurniasih &Juwita (2021).…”
Section: Discussionmentioning
confidence: 60%
“…For example, in this review a study by Alonso-Castro et al, 2021 identi ed anxiety and tremors, as common symptoms of an adverse reaction to some herbs, and in some cases, these symptoms can be severe enough to require hospitalization. Alonso-Castro et al, 2021 also identi ed insomnia, hallucinations, and depression as other severe side effects that can be caused by herbal medicines, especially if they are taken in high doses or used improperly (Tripathi & Bahuguna, 2022). Another study in this review by Aprilio & Wilar, (2021) observed that It's important to note that some herbs can interact with prescription medications, leading to severe side effects, such as hypotension, hyperglycemia, and constipation, a nding corroborated by Kim et al, 2021.…”
Section: Discussionmentioning
confidence: 62%
“…Since ancient times, this plant is known for its medicinal properties. 49,50 The aqueous extract of leaves shows significant reduction in blood sugar level in both normal and alloxan induced diabetic rats .Significant reduction in fasting blood glucose, uronic acid, total amino acid, total cholesterol, triglyceride and total lipid indicate the hypoglycemic and hypolipidemic effects of tulsi in diabetic rats. 51,52 Oral administration of plant extract (200 mg/kg) for 30 days leads to decrease in the plasma glucose level.…”
Section: Ocimum Sanctum L (Lamiaceae)mentioning
confidence: 99%